The prevalence of early‐ and late‐onset bacterial, viral, and fungal respiratory superinfections in invasively ventilated COVID‐19 patients. Issue 5 (4th January 2022) - Paparoupa, Maria; Aldemyati, Razaz; Roggenkamp, Hannes; Berinson, Benjamin; Nörz, Dominik; Olearo, Flaminia; Kluge, Stefan; Roedl, Kevin; de Heer, Geraldine; Wichmann, Dominic
Abstract: The role of respiratory superinfections in patients with coronavirus disease 2019 (COVID‐19) pneumonia remains unclear. We investigated the prevalence of early‐ and late‐onset superinfections in invasively ventilated patients with COVID‐19 pneumonia admitted to our department of intensive care medicine between March 2020 and November 2020. Of the 102 cases, 74 (72.5%) received invasive ventilation and were tested for viral, bacterial, and fungal pathogens on Days 0–7, 8–14, and 15–21 after the initiation of mechanical ventilation. Approximately 45% developed one or more respiratory superinfections. There was a clear correlation between the duration of invasive ventilation and the prevalence of coinfecting pathogens. Male patients with obesity and those suffering from chronic obstructive pulmonary disease and/or diabetes mellitus had a significantly higher probability to develop a respiratory superinfection. The prevalence of viral coinfections was high, with a predominance of the herpes simplex virus (HSV), followed by cytomegalovirus. No respiratory viruses or intracellular bacteria were detected in our cohort. We observed a high coincidence between Aspergillus fumigatus and HSV infection. Gram‐negative bacteria were the most frequent pathogen group. Klebsiella aerogenes was detected early after intubation, while Klebsiella pneumoniae and Pseudomonas aeruginosa were related to a prolonged respiratory weaning. Key points: In our cohort, approximately 45% of the invasively ventilated COVID‐19 patients developed a respiratory bacterial, viral, and/or fungal superinfection within 3 weeks after intubation. The most prevalent group of pathogens were Gram‐negative bacteria.